Lamprologus markerti, a new lamprologine cichlid (Teleostei: Cichlidae) endemic to the lower Congo River in the Democratic Republic of Congo, west-central Africa - Tougas, Stephanie; Stiassny, Melanie L.j. (Zootaxa, 2014)
A new Lamprologus is described from the lower Congo River (LCR) in the Democratic Republic of Congo. Lamprologus markerti, new species, is readily distinguished from L. tigripictilis and L. werneri, the LCR endemic lamprologines with which it was once taxonomically conflated, in the possession of a reduced number of gill rakers on the first arch (9–11 versus 12–17), a longer head (32.1–34.7% SL versus 29.3–31.9 and 29.1–32.9% SL, respectively), and a longer predorsal length (33.0–35.9% SL versus 29.3–32.7 and 28.5–32.6% SL, respectively). Further, L. markerti lacks a second intestinal loop present in both L. tigripictilis and L. werneri, and has a highly reduced infraorbital series often consisting of a single first infraorbital (lachrymal) element.